International financial reporting standards and earnings Quality: the myth of voluntary vs. mandatory adoption - Nina Günther; Bernhard Gegenfurtner; Christoph Kaserer; Ann-Kristin Achleitner (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2009)
We revisit evidence whether incentives or IFRS drive earnings quality changes, analyzing a large sample of German firms in the period from 1998 to 2008. Consistent with previous studies we find that voluntary and mandatory adopters differ distinctively in terms of essential firm characteristics and that size, leverage, age, bank ownership and ownership concentration influenced the decision to voluntarily adopt IFRS. However, regardless of the decision to voluntarily adopt IFRS, we find that conditional conservatism increased under IFRS for both groups of adopters, while evidence does not suggest an increase in value relevance under IFRS. Results on earnings management in the post-adoption period are mixed. While income smoothing decreases for voluntary but not for mandatory adopters, discretionary accruals only decrease for mandatory but not for voluntary adopters. However, further analyses suggest that the capital market environment and the economic cycle during the adoption period seem to be a more powerful explanation for this evidence than voluntary or mandatory IFRS adoption. Therefore, we conclude that incentives to voluntarily adopt IFRS did not unambiguously dominate accounting standards in determining earnings quality in the case of German firms.
Keywords: G14; M4; 330; IAS regulation; IFRS; corporate ownership structures; insider ownership; incentives; earnings quality